A Study on the perception of POKM as the organizational knowledge sharing enabler - Lee, Angela Siew Hoong *; Lim, Tong Ming * (Emerald Open Access, 2015)
Knowledge is asset to many knowledge-driven companies in a globally competitive business eco-system. Companies that are able to capture and reuse knowledge efficiently claim that higher quality products and services can be realized in lower cost and time. Researches on factors that motivate successful knowledge practices using Knowledge Management Systems (KMS) have been well investigated. However, factors on people, organization and technology may vary for organizations of different sizes in countries with different culture. In this study, the case organization failed to achieve some of the goals such as knowledge sharing among employees and creation of new skills and knowledge. This research carried out a detailed study on POKM, a tailored made KMS used by a Malaysian IT Shared Services Company. This study investigates the perception of knowledge workers toward technological characteristics of POKM. The study examines the POKM system quality, perception of POKM user interface, quality of content management offered by POKM, POKM functions, user satisfaction toward POKM and perceived POKM benefit among knowledge workers. The research investigates a IT Shared Services Company in Malaysia. Interview with knowledge workers in the organization takes place before questionnaire survey is distributed to all the participants. This paper presents an in-depth analysis on the interviewees’ responses. The outcome of the interview content is used as the basis to design the questionnaire survey. The outcomes of the research show that the quality of POKM is stable, easy to use and organization of the content is rated good. However, POKM has poor response time and search capability. The content is found to be difficult to locate in the POKM but most participants agree that knowledge stored in the POKM is helpful, can be accessed anytime and anywhere and useful for their day-to-day job. As for the user interface, POKM is not very pleasant to use with a weak set of functions and features in particular social networking feature is not available. For user satisfaction towards POKM, it is shown that users are not satisfied with the efficiency and effectiveness of the systems. However, employees generally are satisfied with ease of access and download features. In term of perceived POKM benefits, users agree that POKM is an enabler for acquiring new knowledge and innovative ideas, managing and storing knowledge, and accomplishing tasks more efficiently. Lastly, knowledge users agree that POKM functions enable knowledge networking, sharing, and creation in the organization